Understanding leptin-dependent regulation of skeletal homeostasis - Motyl, Katherine J. (2012)
Despite growing evidence for adipose tissue regulation of bone mass, the role of the adipokine leptin in bone remodeling remains controversial. The majority of in vitro studies suggest leptin enhances osteoblastic proliferation and differentiation while inhibiting adipogenic differentiation from marrow stromal cells. Alternatively, some evidence demonstrates either no effect or a pro-apoptotic action of leptin on stromal cells. Similarly, in vivo work has demonstrated both positive and negative effects of leptin on bone mass. Most of the literature supports the idea that leptin suppresses bone mass by acting in the brainstem to reduce serotonin-dependent sympathetic signaling from the ventromedial hypothalamus to bone. However, other studies have found partly or entirely contrasting actions of leptin. Recently one study found a significant effect of surgery alone with intracerebroventricular administration of leptin, a technique crucial for understanding centrally-mediated leptin regulation of bone. Thus, two mainstream hypotheses for the role of leptin on bone emerge: 1) direct regulation through increased osteoblast proliferation and differentiation and 2) indirect suppression of bone formation through a hypothalamic relay. At the present time, it remains unclear whether these effects are relevant in only extreme circumstances (i.e. models with complete deficiency) or play an important homeostatic role in the regulation of peak bone acquisition and skeletal remodeling. Ultimately, determining the actions of leptin on the skeleton will be critical for understanding how the obesity epidemic may be impacting the prevalence of osteoporosis.